2007
DOI: 10.1111/j.1348-0421.2007.tb03901.x
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of GB Virus C Co‐Infection in Human Immunodeficiency Virus Type 1‐Infected Individuals

Abstract: Several reports have documented a better prognosis for HIV‐1‐infected patients co‐infected with GBV‐C, while other reports have contradicted such findings with the result that this issue remains controversial. We attempted to clarify the complicated status of the effect of GBV‐C co‐infection on HIV‐1‐infected patients. GBV‐C RNA was detected in 37 samples in 182 HIV‐1‐infected patients (20.3%) using RT/nested PCR. Of these, 3 were determined to be GBV‐C genotype 1, 12 were genotype 2, and the remaining 22 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 29 publications
4
11
2
1
Order By: Relevance
“…This in vitro observation was not corroborated in the present study. Instead, RANTES and TNF-α levels were frequently lower in HIV-1 + GBV-C + co-infected patients compared to HIV-1 + GBV-C -individuals, similar to a report by Hattori et al [8], who found lower RANTES levels in HIV-1 + GBV-C+ co-infected patients compared to non-coinfected HIV-1 patients. Interestingly, GBV-C coinfection appeared to restore leptin levels in HIV-1-infected patients (Figure 1).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…This in vitro observation was not corroborated in the present study. Instead, RANTES and TNF-α levels were frequently lower in HIV-1 + GBV-C + co-infected patients compared to HIV-1 + GBV-C -individuals, similar to a report by Hattori et al [8], who found lower RANTES levels in HIV-1 + GBV-C+ co-infected patients compared to non-coinfected HIV-1 patients. Interestingly, GBV-C coinfection appeared to restore leptin levels in HIV-1-infected patients (Figure 1).…”
Section: Discussionsupporting
confidence: 73%
“…In his study, a significant reduction in the mean HIV-1 load was observed in GBV-C co-infected patients, without differences in CD4 + cell counts (Table 2). A negative correlation between plasma GBV-C and HIV-1 load has been reported [8]; however, this aspect was not evaluated in the current study.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Despite a nonnegligible blood prevalence in healthy persons, that is 1% to 5% in developed countries and up to 20% in developing countries, and higher values in immunocompromised patients, both natural history and potential implication of pegiviruses in host’s health are largely unknown despite their identification more than 20 years ago . Of note, however, human immunodeficiency (HIV)‐HPgV association studies were extensively explored, due to a possible beneficial effect in HIV infection motivating investigations about HIV‐HPgV interactions at the molecular level . Mechanisms of viral persistence and host‐immune modulation remain also poorly characterized .…”
Section: Introductionmentioning
confidence: 99%
“…Также образцы сыворотки крови тестировали на GBV-C RNA (вируса, ранее известного под названием вирус гепатита G) методом ПЦР, совмещенной с обратной транскрипцией по протоколу, описанному J. Hattori с соавт. [6].…”
Section: материал и методы исследованияunclassified